HISTOLOGICAL CHANGES IN HIBISCUS ROSA-SINENSIS ENDORSE ACCLIMATION AND PHYTOREMEDIATION OF INDUSTRIALLY POLLUTED SITES - A. Noman; M. Aqeel; M. T. Javed; S. Zafar; Q. Ali; W. Islam; M. K. Irshad; M. Buriro; H. Kanwal; N. Khalid; S. Khan (Journal of Animal and Plant Sciences, 2017)
Addition of undesired effluents to the environment has resulted in massive destruction of the ecosystem due to the persistent nature of the toxicants. The growth pattern of the plants species growing in urban and sub-urban areas are being affected negatively by various pollutants. In order to adapt and survive in hostile environment, different species exhibits a number of transformations and as a result some species restrain better adaptability and growth. The present study was carried out to investigate the histological alterations as an adaptive response as well as soil and air cleaning characteristics of different Hibiscus cultivars against industrial effluents. The root and stem fresh samples of Hibiscus cultivars were collected from polluted areas of Faisalabad, Punjab, Pakistan. The transverse sections of the root and stem samples were stained and observed by using light microscopy. The presented data clearly depict altered anatomical features depending upon presences of toxicants in the rhizosphere. The modified anatomical attributes like thick stem epidermis, increased epidermal cell  area  high vascular tissue and enhanced cortical cell area in H. rosa-sinensis cv. Cooperi alba  and Lemon chiffon respectively confer the better adaptation to polluted conditions. The knowledge is likely to be helpful for devising plant based decontamination strategies for industrially polluted environment.
Keywords: Acclimation; Hibiscus cultivars; industrial effluents; Tissue modifications; Phytoremediation